Development of a decision support system for trypanocidal drug control of bovine trypanosomosis in Africa - Gu, Y.; Gettinby, George; McKendrick, I.; Murray, M.; Peregrine, A.S. (Elsevier, 1999)
During this century livestock production has increased massively through the improved ability to diagnose, treat, control and prevent certain diseases. Despite these advances, disease remains a major constraint to livestock production and welfare throughout the world. In many instances, this is a result of failure to properly apply methods that are already available. TrypsChemo is an expert system that attempts to aid the applicaiton of veterinary knowledge to disease management. It has been designed to maximise the effectiveness and cost efficiency of the different trypanocidal drug regimes currently available for prophylaxis and treatment of tsetse-transmitted bovine trypanosomosis in Africa. This paper describes the design of TrypsChemo, the properties of the system, and illustrates how it can be used to support decision making for trypanocidal drug control. The system is currently undergoing a structured evaluation by potential users in Africa.